3N-AHP Model, the New Multiactor Multicritera for the Selection of Optimal Corridors of the Line Infrastructure Facilities. (2016) - Hot, Izet; Manic, Nazim; Šerifi, Veis
Abstract: In this paper is developed a complex model for the evaluation and selection of the optimum spatial solutions of the corridor line infrastructural facility, which is characterized by multiactor and multicriteria approach. The model is based on the multiactor multicriteria analysis methodology (MAMCO - The Multi Actor Multi Criteria Analysis Methodology) where the relevant decision-making actors, verified by stakeholder analysis (The Stakeholdes analysis), based on the criteria of evaluation that are sorted in the proper hierarchy and whose relevance is confirmed by the factor analysis (the Factor analysis) using the evaluation and ranking of alternatives of the AHP method (the Analityc Hierarchy Process), which was selected by intelligent access with the help of decision tree (decision Tree), offered from a set of alternatives to choose the optimum solution, and the accuracy of their selection check by sensitivity analysis (sensitivity analisys) .